2019
DOI: 10.1007/s11033-019-05092-z
|View full text |Cite|
|
Sign up to set email alerts
|

Propidium monoazide–polymerase chain reaction for detection of residual periprosthetic joint infection in two-stage revision

Abstract: False negative culture results in periprosthetic joint infection (PJI) are not uncommon particularly when patients have received long term antibiotics. Polymerase chain reaction (PCR) has a lower specificity partly due to detection of residual DNA from dead bacteria. Propidium monoazide (PMA) prevents DNA from dead bacteria from being amplified during the PCR. This study aimed to determine the role of PMA in PCR for diagnosis of PJI. Clinical samples were tested by PCR with and without prior treatment with PMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Therefore, to study their potential microbiota, further developments in bioinformatics and more targeted methods, such as qPCR, might be required. Future studies may consider use of propidium monoazide-polymerase chain reaction, which prevents amplification of nucleic acids from free or dead microorganisms [ 49 ]. To undertake such assays, we must identify taxa of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to study their potential microbiota, further developments in bioinformatics and more targeted methods, such as qPCR, might be required. Future studies may consider use of propidium monoazide-polymerase chain reaction, which prevents amplification of nucleic acids from free or dead microorganisms [ 49 ]. To undertake such assays, we must identify taxa of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors using an in vitro biofilm model, have shown that PMA treatment enhanced the observed differences after chlorhexidine rinse as compared to non‐PMA treated samples (Exterkate et al, 2014 ). In the field of orthopedic surgery, when PMA in combination to PCR was compared to culture and standard PCR techniques for the detection of residual periprosthetic joint infection, an enhancement of the specificity and sensitivity of 89% and 79% respectively, was reported in PMA‐treated samples (Askar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these dyes, PMA is the most widely used dye for the preselection of the viable microorganisms and it has been reported in some studies that PMA showed higher sensitivity than EMA in the detection of viable microbial cells ( a strong covalent nitrogen-carbon bond. This modification results in the structural changes and insolubility of the DNA, which leads to the loss of the DNA during the extraction procedure and inaccessibility of the DNA for elongation by DNA polymerase (Askar et al, 2019;Nocker et al, 2006). Therefore, the DNA template in dead bacteria pretreated with PMA fails to amplify during PCR procedure (Figure 4).…”
Section: Nucleic Acid Amplification-based Detection Methodsmentioning
confidence: 99%